(E)-2,2 '-[3-(2-Nitrophenyl)prop-2-ene-1,1-diyl]bis(3-hydroxy-5,5-dimethylcycloh ex-2-en-1-one) - Cha, Joo Hwan; Kim, Young Hee; Min, Sun-Joon; Cho, Yong Seo; Lee, Jae Kyun (WILEY-BLACKWELL, 2011)
In the title compound, C25H29NO6, each of the cyclohexenone rings adopts a half-chair conformation. Each of the pairs of hydroxy and carbonyl O atoms are oriented to allow for the formation of intramolecular O-H center dot center dot center dot O hydrogen bonds, which are typical of xanthene derivatives. The nitro group is rotationally disordered over two orientations in a 0.544 (6):0.456 (6) ratio. In the crystal, weak intermolecualr C-H center dot center dot center dot O hydrogen bonds link molecules into layers parallel to the ab plane.